Analysis on Photovoltaic Energy-Assisted Drying of Green Peas - Onur Taşkın; Nazmi İzli; Ali Vardar (International Journal of Photoenergy)
A photovoltaic energy-assisted industrial dryer has been analyzed. The dryer has been tested in various weather and working conditions with 3 kg of green peas from 75.6% initial moisture content to 20% final moisture content (w.b.). The effect of various drying air temperatures at three levels (40, 50, and 60°C) and two distinct air velocities (3 m/s and 4 m/s) was examined. Drying performance was assessed with regard to criteria including drying kinetics, specific and total energy consumption, and color and rehydration ratio. The results have proved that total drying duration reduces as air velocity rate and drying air temperature raise. Relying upon the drying durations, the generation performances of photovoltaic panels were between 5.261 and 3.953 W. On the other part, energy consumptions of dryer were between 37.417 and 28.111 W. The best specific energy consumption was detected in 50°C at 3 m/s for 600 minutes with 7.616 kWh/kg. All drying conditions caused darkening as color parameters. Rehydration assays have showed that rehydrated green peas attained higher capacity with raised air temperature and air velocity.